Utilizing the Health Belief Model Theory to Forecast Early Breastfeeding Initiation in Karanganyar Regency, Central Java - Devi Indrawati; Argyo Demartoto; Bhisma Murti (Journal of Health Promotion and Behavior, 2024)
Background: Early initiation of breastfeeding has the potential to reduce the risk of neonatal death. Babies who do not start breastfeeding within the first hour after birth have a higher risk of death. This study aimed to determine the relationship between the Health Belief Model construct and early breastfeeding initiation behavior. Subjects and Method: The study was conducted in February-March 2024 with a sample of 200 mothers who had children aged 0-3 months at Posyandu in the Karanganyar Regency working area. This study used an observational analytic design with a cross-sectional study approach. Sampling used was fixed disease sampling. The dependent variable was early initiation of breastfeeding and the independent variables were perceived vulnerability, perceived severity, perceived benefits, perceived barriers, cues to action and self-efficacy. The data were collected using questionnaire and analyzed using multiple logistic regression analysis. Results: This study provided empirical evidence that a number of constructs in the Health Belief Model can be used as predictors of early breastfeeding initiation. Mothers who have a high perceived vulnerability (OR= 4.48; CI 95%= 1.12 to 17.89; p= 0.034), high perceived severity (OR= 4.14; CI 95%= 1.16 to 14.87; p=0.029), high perceived benefit (OR= 4.37; CI 95%= 1.15 to 16.56; p=0.030), and high self-efficacy (OR= 16.76; CI 95%= 3.91 to 71.79; p <0.001) showed a positive relationship with increasing early breastfeeding initiation behavior. Conclusion: There is a positive relationship between perceived vulnerability, perceived severity, perceived benefits, and self-efficacy with early breastfeeding initiation behavior.